Cervical Cancer: Understanding Its Causes, Risk Factors, and Preventive Measures - Anshika Rosha; Ritu Jhakar (International Journal of Oncological Nursing and Practices, 2025)
Cervical cancer is a form of cancer that begins in the cervix, the lower portion of the uterus, due to abnormal cell growth that can spread or invade other areas of the body. In its early stages, cervical cancer usually shows no obvious symptoms, which is why regular screenings are essential for detecting it early. As the cancer advances, symptoms such as pelvic pain, unusual vaginal bleeding, and pain during intercourse may occur. While bleeding after sex is not always a serious concern, it can be a sign of cervical cancer. The main cause of cervical cancer is a persistent infection with specific strains of Human Papillomavirus (HPV), especially types 16 and 18, which account for about 70% of cervical cancer cases worldwide. However, not everyone with HPV will develop cervical cancer, as the infection is common and usually clears up on its own. In addition to HPV, various other risk factors contribute to cervical cancer, such as smoking, a compromised immune system, the use of birth control pills, having multiple sexual partners, and early sexual activity. Genetic factors can also increase the likelihood of developing the disease. Cervical intraepithelial neoplasia (CIN), a precancerous condition, typically develops over a period of 10 to 20 years before cervical cancer can occur. Squamous cell carcinomas account for approximately 90% of cervical cancer cases, while adenocarcinomas represent around 10%, with other types being rare. Early detection through screening and vaccination against HPV is key to preventing the onset of cervical cancer, as these measures can help reduce the impact of high-risk HPV types responsible for the majority of cases.
Keywords: Human Papillomavirus (HPV); Risk factors; cervical cancer; cervical intraepithelial neoplasia (CIN); squamous cell carcinoma